Human values and natural systems - Rolston, Holmes, 1932-2025, author; Taylor & Francis, publisher (Colorado State University. Libraries, 1998)
What human values are earned by natural systems? I can answer that question directly while I indirectly address a deeper question. Are values in nature objective or subjective? Some values (the nutrition in a potato) seem objectively there, while others (the eagle as a national symbol) seem merely assigned. Either way, certain experiences that humans find to be valuable require and are carried by natural things. As we examine the types of natural values, we can wonder whether-at times at least-value intrinsic in nature enables humans to enjoy these values.
Keywords: Endangered Species Act; ecology; values; nature; biosystem; culture; economics; recreation; science; aesthetics